2019
DOI: 10.1175/jcli-d-18-0351.1
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal Change in the Intensity of Interannual Variation of Spring Precipitation over Southern China and Possible Reasons

Abstract: The intensity of interannual variation of spring precipitation over southern China during 1979–2014 and possible reasons for it are investigated in this paper. There is a significant interdecadal change in the intensity of interannual variation of spring precipitation over southern China around 1995/96. The intensity of interannual variation of spring rainfall over South China is stronger during 1979–95 than that during 1996–2014. The possible reason may be the larger amplitude of the sea surface temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
(49 reference statements)
1
12
0
Order By: Relevance
“…2016; X. F. Wu and Mao 2016; Xu et al. 2019). In fact, the early spring rainfall over the SEETP tends to vary in‐phase with that over South China (Figures 2 and 3d).…”
Section: Discussionmentioning
confidence: 99%
“…2016; X. F. Wu and Mao 2016; Xu et al. 2019). In fact, the early spring rainfall over the SEETP tends to vary in‐phase with that over South China (Figures 2 and 3d).…”
Section: Discussionmentioning
confidence: 99%
“…The extreme precipitation volumes and intensities are relevant to various problems of climatology and hydrometeorology (see, for example, [44][45][46][47]). Traditionally, these phenomena are investigated for different geographical regions or countries [48,49]. In particular, the issue of determining threshold values, the excess of which leads to the extreme events, for example, in daily rainfalls or their intensities, is the key point of the study.…”
Section: Comparison Of Gg-based Statistical Test and Peaks Over Thresmentioning
confidence: 99%
“…It can also be defined as the ratio of precipitation rate to the vertical integral of condensation and deposition rates derived from the cloud microphysical budget [9,31,32]. e PE also serves as a crucial factor in the parameterization of cumulus convection [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…With increasing water vapor in the lower troposphere, the intensity of moist convection lessens and mass exchange between the boundary layer and the middle troposphere decreases to balance the global hydrological cycle [32,33]. Xu et al [36] suggested that the interdecadal change in the intensity of spring rainfall variations over southern China can be attributed to the reduced amplitude of SSTAs in the West Pacific after 1996.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation